IMPROVEMENT OF ROTATIONAL KNEE STABILITY USING LATERAL EXTRA-ARTICULAR TENODESIS AND ANTEROLATERAL LIGAMENT RECONSTRUCTION: INDICATIONS, COMPLICATIONS, AND COMPARISON OF TECHNIQUES — A REVIEW OF THE LITERATURE - Maciej Sokołowski; Karolina Oskroba; Estera Graczyk; Joanna Kryślak; Katarzyna Skibicka; Adam Solarz; Szymon Szabelski; Jakub Filip Turcza (International Journal of Innovative Technologies in Social Science, 2025)
The anterior cruciate ligament (ACL) is one of the most frequently injured structures of the knee. To restore joint function, ACL reconstruction surgery is commonly performed. However, despite successful reconstruction, some patients fail to regain full function due to residual rotational instability. Procedures aimed at improving rotational stability include anterolateral ligament reconstruction (ALLR) and lateral extra-articular tenodesis (LET). This article reviews the anatomy of the ACL and the anterolateral complex. The techniques of ALLR and LET are described, and the two methods are compared. Indications, complications, clinical outcomes, and potential long-term effects of these procedures are also discussed.